Tantangan Hukum Humaniter Dalam Menghadapi Perang Asimetris: Analisis Dan Solusi - Wahyudi, Hadi; Khakim, Khalimul; Susilo, Tarsius; Zulkifli; Tunggul Wiratama, Wahyu (Shofanah Media Berkah, 2025)
Asymmetric warfare involving state and non-state actors in modern conflicts poses serious challenges to the implementation of International Humanitarian Law (IHL). This study analyzes the mismatch in the identification of combatants, the problems surrounding civilian protection, and accountability for violations within the context of asymmetric conflicts. The findings indicate that the ambiguity of combatant status and the strategic use of civilians as human shields hinder the application of fundamental IHL principles, such as distinction and proportionality. Moreover, international legal enforcement mechanisms continue to face significant limitations in prosecuting violations, particularly those committed by non-state actors. This study recommends strengthening adaptive legal frameworks and establishing effective accountability mechanisms to ensure the protection of human rights and legal order in asymmetric conflict situations. The research contributes significantly to the development of humanitarian law that is responsive to the dynamics of contemporary conflicts.